A common factor regulates skeletal and cardiac alpha-actin gene transcription in muscle. - Muscat, G E (1988)
The skeletal and cardiac alpha-actin genes are coexpressed in muscle development but exhibit distinctive tissue-specific patterns of expression. We used an in vivo competition assay and an in vitro electrophoretic mobility shift assay to demonstrate that both genes interact with a common trans-acting factor(s). However, there was at least one gene-specific cis-acting sequence in the skeletal alpha-actin gene that interacted with a trans-acting factor which was not rate limiting in the expression of the cardiac alpha-actin gene. The common factor(s) interacted with several cis-acting regions that corresponded to sequences that are required for the transcriptional modulation of these sarcomeric alpha-actin genes in muscle cells. These regulatory regions contained the sequence motif CC(A + T-rich)6GG, which is known as a CArG box. Results of in vivo competition assays demonstrated that the factor(s) bound by the skeletal alpha-actin gene is also essential for the maximal activity of the cardiac alpha-actin, simian virus 40 (SV40), alpha 2(I)-collagen, and the beta-actin promoters in muscle cells. In contrast, fibroblastic cells contained functionally distinct transcription factor(s) that were used by the SV40 enhancer but that did not interact with the sarcomeric alpha-actin cis-acting sequences. The existence of functionally different factors in these cell types may explain the myogenic specificity of these sarcomeric alpha-actin genes. Results of in vitro studies suggested that both the sarcomeric alpha-actin genes interact with the CArG box-binding factor CBF and that the skeletal alpha-actin promoter contains multiple CBF-binding sites. In contrast, CBF did not interact in vitro with a classical CAAT box, the SV40 enhancer, or a linker scanner mutation of an alpha-actin CArG box. Furthermore, methylation interference and DNase I footprinting assays demonstrated the precise sites of interaction of CBF with three CArG motifs at positions -98, -179, and -225 in the human skeletal alpha-actin gene.